Analyzing nature's protective design: The glyptodont body armor. (June 2018) - du Plessis, Anton; Broeckhoven, Chris; Yadroitsev, Igor; Yadroitsava, Ina; le Roux, Stephan Gerhard
Abstract: Many animal species evolved some form of body armor, such as scales of fish and bony plates or osteoderms of reptiles. Although a protective function is often taken for granted, recent studies show that body armor might comprise multiple functionalities and is shaped by trade-offs among these functionalities. Hence, despite the fact that natural body armor might serve as bio-inspiration for the development of artificial protective materials, focussing on model systems in which body armor serves a solely protective function might be pivotal. In this study, we investigate the osteoderms of Glyptotherium arizonae, an extinct armadillo-like mammal in which body armor evolved as protection against predators and/or tail club blows of conspecifics. By using a combination of micro-computed tomography, reverse-engineering, stress simulations and mechanical testing of 3D printed models, we show that the combination of dense compact layers and porous lattice core might provide an optimized combination of strength and high energy absorption.